Study of dissolved copper (II) speciation at coastal water of Peninsular Malaysia - Godon, Edrianna; Mohamed, Khairul Nizam; Gani, Mohamad Azrul; Johan, Shamsuddin (Oriental Scientific Publishing Company, 2018)
Samples from Perhentian and Pangkor Island Marine Park, Peninsular Malaysia were analyzed for Cu(II) speciation by using CLE-AdCSV. Northeast monsoon effect was studied in Perhentian and compared with Pangkor. Excess concentration of CuL found for all stations in both islands showed >99.5% of total dissolved Cu (dCu) was bound to Cu (II) complexing ligands. The log K’CuL>12 data indicated the presence of strong natural ligands (L1) in Perhentian Island. Lower log K’ (log K’=10 to 12) and two types of ligands (L1 and L2) were found in Pangkor Island. The ratio of CuL/dCu was analysed to see the ligand distributions, and saturation rate with dissolved Cu. Statistical analysis showed weak relationship between the in-situ parameters to log K’ values (p>0.05). The log K’CuL (PP: 12.00-12.96, PG: 10.93-12.840) data suggested that the dissolved Cu are used by marine organisms, thus preventing the free Cu2+ ions to be produced.